New trends in computational electromagnetics - Ergül, Özgür (ACES series on computational electromagnetics and engineering., 2019)
The authors present a broad overview of the recent efforts in computational electromagnetics to develop and implement more robust, accurate and efficient algorithms. With the recent improvement in available computing power, this is a timely overview of a rapidly developing subject.